Deciphering the fate of antibiotic resistance genes in norfloxacin wastewater treated by a bio-electro-Fenton system. (November 2022) - Li, Shengnan; Gao, Mingsi; Dong, Heng; Jiang, Yuxin; Liang, Wanting; Jiang, Jiwei; Ho, Shih-Hsin; Li, Fengxiang
Graphical abstract: Highlights: Bio-electro-Fenton systems removed NFLX reached 79.8 % in 48 h reaction time. The change of NFLX concentration can affect the potential of the anode and cathode. Actinobacteria may be more resistant to antibiotics. The ko02010 pathway upregulated with the addition of NFLX. The antibiotic resistance mechanisms varied strongly for diverse bacterial species. Abstract: The misuse of antibiotics has increased the prevalence of antibiotic resistance genes (ARGs), considered a class of critical environmental contaminants due to their ubiquitous and persistent nature. Previous studies reported the potentiality of bio-electro-Fenton processes for antibiotic removal and ARGs control. However, the production and fate of ARGs in bio-electro-Fenton processes triggered by microbial fuel cells are rare. In this study, the norfloxacin (NFLX) average residual concentrations within two days were 2.02, 6.07 and 14.84 mg/L, and the average removal efficiency of NFLX was 79.8 %, 69.6 % and 62.9 % at the initial antibiotic concentrations of 10, 20 and 40 mg/L, respectively. The most prevalent resistance gene type in all processes was the fluoroquinolone antibiotic gene. Furthermore, Proteobacteria was the dominant ARG-carrying bacteria. Overall, this study can provide theoretical support for the efficient treatment of high antibiotics-contained wastewater by bio-electro-Fenton systems to better control ARGs from the perspective of ecological security.